Genetic Diversity of HPV 16 and HPV 18 Based on Partial Long Control Region in Iranian Women - Mina Mobini Kesheh; Mohadeseh Barazandeh; Amir Kaffashi; Mohammad Kazem Shahkarami; Seyed Alireza Nadji (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Human papillomavirus (HPV) 16 and HPV 18 account for 75% of all cervical cancers. The L1 gene, encoding the major surface protein (MSP), is used to classify HPV types (lineages and sublineages), genotypes, and intratypic variants. Therefore, this study aimed to investigate the lineages, sublineages, genetic variabilities, and mutation effects on transcription factor binding sites by using partial sequences of the HPV 16 and HPV 18 long control regions (LCRs) in these samples. Materials and Methods. After DNA isolation from 56 positive samples, the LCR of HPV 16 and HPV 18 were amplified using specific primers, and phylogenetic trees were drawn through MEGA X. Compared to the reference sequences, single nucleotide polymorphisms (SNPs) were identified. The transcription binding sites were also evaluated using the online PROMO database. Results. The LCRs of 52 samples were successfully sequenced. Overall, 81.58% of all HPV 16 variants belonged to the D1 sublineage, followed by A4 (13.16%), A1 (2.63%), and C1 (2.63%) sublineages. All HPV 18 isolates belonged to A sublineage, 92.85% to A3 sublineage, and 7.15% to A4 sublineage. Out of 27 SNPs in the HPV 16 LCR, A7382T, T7384G, C7387T, C7393G, A7431G, T7448C, and C7783A were HPV 16-specific. Also, among 14 SNPs in the HPV 18 LCR, C7577A and A7943T were not previously reported. An insertion (C) between 7432 and 7433 positions was identified in all studied HPV 16 variants. Besides, most of the HPV 16 mutations were embedded in the YY1, TFIID, Oct-2, and NF-1 binding sites, while c-Fos and MBF1, as the most common binding sites, were affected by HPV 18 LCR mutations. Conclusion. The present results showed that D1 and A3 were the dominant sublineages of HPV 16 and HPV 18, respectively. Therefore, women infected with these variants need to be examined in further longitudinal studies to obtain more information about the oncogenic potential of these dominant variants in Iran. Besides, YY1, TFIID, Oct-2, NF-1, c-Fos, and MBF1 were the most frequent binding sites, which were influenced by the mutations.